Tafamidis treatment for patients with transthyretin amyloid cardiomyopathy - Maurer, Mathew S.; Kristen, Arnt (The New England journal of medicine, 2018)
Original Article from The New England Journal of Medicine — Tafamidis Treatment for Patients with Transthyretin Amyloid Cardiomyopathy